(3VhA GdSbWs - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s; (3CHh GdYdGA GdeYQj , CHh GdYdGA CMeO Hf YHO Gddg Hf SdjeGf GdJfhMj GdeYQj,J (B449 (3g` s ((3eMeO Hf eMeO GdRjGOj s)
(3ChdgG (B:s
(3bGd GdTjN CHhGdYdGA CeG HYO, aEf GdTYQGA cCaQGS hSCdfj Cf CTQM dg eG GSJYLe Ydjg ef GdcJGH HGdeYQha HSbW GdRfO s
(3BNQgG (B:s
(3CYfO Gddg NHQ ef MjGJj hWhd PgGHgG YjT eQjM JYddfj CJTajfj aPQfj dYdj CSJQjM hJSJQjM Je SbW GdRfO HVhFg, hced hGdMeO ddg hMOg s
(3GfXQ aj GdLRA GdChd GdCQbGe (B532-534 (3COHs
(3HChdgG Jedc SfI (B1028(3g` hBNQ HeUQ SfI (B1029(3g`s
(3aj Chd GdeNWhWI Gfg TQM GdJHQjRj hGdUMjM eG CKHJfGg hdYd SHH Gdhge jYhO Edi Cf GdJHQjRj GSJhYH (B"(3GdVhA(B" (3aj TQMgs
(3gh TQM SbW GdRfO hGdGKfGf dg s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdCOHs